Lomonosov Ridge off Greenland (LOMROG) - Meteorological, Oceanographic and Ship Data Collected Onboard Icebreaker Oden during August 12 through September 19 2007. - Swedish Polar Research Secretariat (Swedish Polar Research Secretariat, 2017)
This data set contains meteorological, oceanographic and ship data collected during the Danish-Swedish expedition Lomonosov Ridge off Greenland (LOMROG), which was an international research cruise using the icebreaker Oden in the waters north of Greenland in August 2007.

This data set contains meteorological, oceanographic and ship data collected during the Danish-Swedish expedition Lomonosov Ridge off Greenland (LOMROG), which was an international research cruise using the icebreaker Oden in the waters north of Greenland.

Data includes meteorological variables: Air temperature, Humidity, Wind direction/speed, Atmospheric pressure.

Oceanographic variables: Sea water temperature, Conductivity, Salinity and Sound velocity.

Ship data: Position, Speed, Course, Water depth.

Further metadata on instrumentation and the individual variables can be found in the info file. Graphics and files describing the route are included in the package.

Quality Information:

Obviously erroneous data (e.g. negative air pressure) have been omitted. No other processing or quality check of the data has been undertaken. Users should be aware of this in further data handling and analysis.

Materialet innehåller meteorologiska, oceanografiska och skeppsdata som samlats in under den danska-svenska expeditionen Lomonosov Ridge utanför Grönland (LOMROG), en internationell forskningskryssning med isbrytaren Oden norr om Grönland, augusti 2007.

This data set contains meteorological, oceanographic and ship data collected during the Danish-Swedish expedition Lomonosov Ridge off Greenland (LOMROG), which was an international research cruise using the icebreaker Oden in the waters north of Greenland.

Data includes meteorological variables: Air temperature, Humidity, Wind direction/speed, Atmospheric pressure.

Oceanographic variables: Sea water temperature, Conductivity, Salinity and Sound velocity.

Ship data: Position, Speed, Course, Water depth.

Further metadata on instrumentation and the individual variables can be found in the info file. Graphics and files describing the route are included in the package.

Quality Information:

Obviously erroneous data (e.g. negative air pressure) have been omitted. No other processing or quality check of the data has been undertaken. Users should be aware of this in further data handling and analysis.
Lomonosov Ridge off Greenland (LOMROG) - Meteorologiska och oceanografiska data, samt skeppsdata, insamlade ombord på isbrytaren Oden från 12 augusti till 19 september 2007 - Lomonosov Ridge off Greenland (LOMROG) - Meteorological, Oceanographic and Ship Data Collected Onboard Icebreaker Oden during August 12 through September 19 2007.
Keywords: Meteorology; Meteorologi; ATMOSPHERE; ATMOSPHERIC WINDS; SURFACE WINDS; ATMOSPHERIC TEMPERATURE; AIR TEMPERATURE; ATMOSPHERIC WATER VAPOR; HUMIDITY; ATMOSPHERIC PRESSURE; SURFACE PRESSURE; OCEANS; SALINITY; CONDUCTIVITY; DENSITY; OCEAN TEMPERATURE; WATER TEMPERATURE; WATER DEPTH; SEAFLOOR TOPOGRAPHY; BATHYMETRY; The icebreaker Oden; Isbrytaren Oden; Environmental Sciences; Miljövetenskap; Meteorology and Atmospheric Sciences; Meteorologi och atmosfärsvetenskap; Oceanography, Hydrology and Water Resources; Oceanografi, hydrologi och vattenresurser; Engineering and Technology; Teknik; Climatology / Meteorology / Atmosphere; Klimatologi och meteorologi; Oceans; Kust och hav